EFFECTS OF SOIL NUTRIENT AVAILABILITY ON ECTOMYCORRHIZAL COMMUNITIES’ DISTRIBUTION IN TWO DIPTEROCARP SPECIES UNDER ELEVATED ATMOSPHERIC CARBON DIOXIDE - Aqilah MB, Nur; Shafini A, Alia; Hidayah J, Nur; Thi, BK; Patahayah, M; Azian, M; Fitri Z, Ahmad; Nizam MS, Mohd (Journal of tropical forest science, 2025)
The consequences of rising atmospheric carbon dioxide (CO₂) level on belowground communities in tropical rainforests continues to be a subject of debate. The main objective of this study was to investigate the distribution of ectomycorrhizal (ECM) fungi and relationship between soil nutrients availability under two different CO₂ concentrations. Free Air Carbon Dioxide Enrichment (FACE) hexagon plot was designed to monitor the impact of CO₂ in tropical rainforest ecosystems at Tekam Forest Reserve, Pahang, Malaysia. Twelve roots and soil samples were collected from two dipterocarp saplings (Shorea lepidota and S. leprosula) in both elevated CO₂ (FACE plot) and control plot conditions. Five soil properties: nitrogen (N), phosphorus (P), potassium (K), carbon (C), and the C:N ratio were analysed. In terms of species distribution, only four species of ECM were found in the FACE plot as opposed to five in the control plot. Unlike Geastrum sp. which was observed in the control plot, Lactarius sp., Russula sp., Tomentella sp., and Cenococcum sp. exist in both control and FACE plots, indicating their adaptability to varying soil nutrient and CO₂ conditions. Then the Detrended Correspondence Analysis (DCA), Principal Component Analysis (PCA), and Canonical Correspondence Analysis (CCA) were employed to establish the relationship between ECM fungi and their host plant, soil nutrient composition and host plant, and combining all parameters, respectively. Shorea lepidota displayed a tendency towards phosphorus in the control plot while S. leprosula showed a preference for higher carbon contents. Tomentella sp. and Cenococcum sp. showed strong association with nitrogen and potassium contents, respectively. Whilst, both Lactarius sp. and Russula sp. were highly associated with C:N ratio. Conclusively, our findings emphasize the need to understand the complex relationship between soil nutrient availability, ECM distribution and elevated atmospheric CO₂ in tropical rainforest ecosystems.